Efectiveness of school-based interventions for preventing tobacco smoking initiation among young people in low and middle-income countries: a systematic review protocol - Logo Darlington Divine; Enuameh Yeetey; Owusu-Dabo Ellis; Adjei George; Singh Arti....et al (BioMed Central, 2023)
This article is published by BioMed Central and is also available at https://doi.org/10.1186/s13643-022-02127-8